Analysis of the Development of Hard Skills, Soft Skills, and Insights in the MBKM Program on Student Self-Determination - Gladis Aminatus Pravita, Swari; Muslih, Basthoumi (Universitas Nusantara PGRI Kediri, 2025)
Research aim: This study tries to analyze the extent to which MBKM program students develop hard skills, soft skills, and insights that are relevant to the self-determination of students of the Management major of Nusantara University PGRI Kediri who participate in the 2024/2025 Odd Semester MBKM program. Design/Methode/Approach: This analysis uses a quantitative method with a quantitative descriptive approach conducted on all students of the Management study program of Universitas Nusantara PGRI Kediri who participate in the 2024/2025 Odd Semester MBKM program. All populations were used as research samples for 43 respondents. The data was carried out using multiple linear regression techniques. Research Finding: The output of this analysis prove that hard skills have no partial effect and have a simultaneous effect on students' self-determination. Meanwhile, soft skills and insights partially and simultaneously affect the self-determination of MBKM students. Theoretical contribution/Originality: From this study, it was found that there were different things from the previous research, where the previous research explained that the hard skill variable did not necessarily have a significant impact on students' self-determination, and the soft skill and insight variables supported previous research Practitionel/Policy implication: These findings emphasize the importance of developing students' soft skills and insights in the MBKM program to increase their self-determination. Higher education institutions need to direct the MBKM program holistically, integrating hard skills, soft skills, and insights to produce competitive graduates and support the achievement of program goals. Research limitation: The current research variable only affects students' self-determination by 86.0%, so other factors need to be further researched.